A case of multiple empyema caused by Streptococcus intermedius. Issue 6 (December 2017) - Kaga, Akihito; Higo, Ryuzaburo; Yoshikawa, Hiroshi; Yokoi, Naoko; Haruyama, Takuo; Komatsu, Hiroaki; Yabe, Ayumi; Kusunoki, Takeshi; Ikeda, Katsuhisa
Abstract: We report the case of a patient with multiple empyema present throughout his body, including chronic sinusitis and chronic suppurative otitis media, as well as subsequent epidural empyema, all caused by Streptococcus intermedius . A 38-year-old man presented with chief complaints of headache, left ear discharge, and nasal congestion. Imaging studies revealed pansinusitis, soft tissue signs in the mastoid cells, and otitis media. The patient was treated with meropenem hydrate, 6 g/day. While clinical findings indicated improvement of the sinusitis, his headache did not improve. Further examination with contrast computerized tomography (CT) 'a chest radiography' blood cultures were performed, and the patient was diagnosed with multiple empyema (with an epidural empyema, pulmonary suppuration) caused by S. intermedius . Subsequent burr hole drainage was implemented to drain the epidural empyema. Long-term administration was required to treat pulmonary suppuration. While they remain rare, there has been a recent upward trend in the frequency of cases in which a young, previously healthy patient has developed multiple empyema throughout their body despite the absence of complicating diseases that pose an immune deficiency risk, such as diabetes or infection with the human immunodeficiency virus (HIV). In order to properly diagnose and treat patients presenting with multiple empyema infection with S. intermedius should be included in the differential diagnosis.